(untitled) (Italian Journal of Public Health, 2008)
Background: In the Italian National Health Service hospital planning was influenced by two aspects: the patients’ freedom to choose their health care provider and the equal distribution of centers spread throughout Italy. While every Italian Region should be able to meet the health needs of its own inhabitants, consistent migration among regions exists. Retrospective studies of cross boundaries patient flows can be useful for health planning purposes, providing precious information about citizens’ preferences, and helping health managers to think about inequality and adjust the offer of care. The aim of this study is to describe cross boundary flows which occurred across all the Italian Regions in 2003. Methods: The hospital discharges for 2003 were obtained from the General Directorate for Health Planning of the Italian Ministry of Health. We analyzed regional cross boundary flows using the Gandy Nomogram. This tool, which assesses patient mobility, can be used to describe regions’ ability to satisfy their internal health demand and their own capability in attracting foreign patients. Results: All of the regions, for the most part, were able to satisfy internal health care demands, and are placed in the upper right corner of the Gandy Nomogram. Umbria, Emilia Romagna, P. A. di Bolzano, Tuscany, Lombardy, Friuli V. Giulia, Lazio, Abruzzo were the regions that appeared to perform best. The Lombardy region attracts the most patients. Conclusions: This study briefly provides an evaluation of hospital supply of services giving indications about patients’ perception of the quality and organization of services. A deeper analysis of patient migration may be undertaken by looking at specific diseases. This kind of research could be useful for planning and maximising supplies when making decisions about healthcare.